DAMPAK UMKM TERHADAP PENYERAPAN TENAGA KERJA DI KOTA BLITAR - Agustina Budi Lestariani (Jurnal Ilmiah Mahasiswa FEB, 2015)
SMEs is one of the sectors that provide the largest contribution in the economy of the community in Blitar city. SMEs is one of the most dominant sector in terms of labor absorption is because the nature of SMEs that do not require higher education but only relying on the skills and tenacity as well as the use of capital that is not too large. In this case, there are many variables that are  used  to analyze  the  labor  absorption among  which  the  number  of business  units  (X1), investments (X2), and production (X3). And of calculating the regression analysis showed that the variables that have a significant and positive impact on employment in Blitar city.Keywords: Smes, Employment, Number Of Business Units, Investment, Production.